Forecasting onion price for Varanasi market of Uttar Pradesh, India - KUMAR, PRAMOD; BADAL, PRAKASH SINGH; PAUL, RANJIT KUMAR; JHA, G K; P, VENKATESH; KAMALVANSHI, KAMALVANSHI; P, ANBUKANI; M, BALASUBRAMANIAN; PATEL, PREETI (The Indian Journal of Agricultural Sciences, 2021)
The onion crop is widely seen as the poor man's vegetable, has the power to change electoral results (Anonymous 2019). In India Onion (Allium cepa) is cultivated in an area of 12.7 lakh ha and produces 215.64 lakh ton. In Uttar Pradesh it is cultivated in an area of 0.25 lakh ha producing 4.23 lakh ton. The study was done during 2020 at IARI, New Delhi. Development of appropriate price forecasting mechanism and dissemination among the farmers would help alleviate problems faced by the farmers and consumers alike. The average price of onion throughout the year, during the study period of 2015-2020, has been fluctuating between ₹ 900-2200/quintal. The ARIMA (0,1,2)(1,0,0) [52] and ARFIMA(3,0,0)-sGARCH (1,1) model were found to be best fit model. However, on the basis of MAPE, MSE, RMSE and Theil's U statistics it was observed that the ARMA-GARCH model outperformed the ARIMA model.